دور الإنتاج الأنظف في تعزيز إستدامة الأعمال دراسة تحليلية لوجهات نظر عينة من المديرين في شركات إنتاج المياه المعدنية في إقليم كوردستان العراق - محمود, عثمان كريم; حنظل, قاسم احمد (Sulaimani Journal for Humanities, 2018)
This research aims at determining the role of by cleaner production in enhancing the sustainability of industrial companies producing mineral water. The research problem consists of the lack of sustainability of the companies that are being studied because they produce bottled drinking water and it is usually believe that they serves sustainability, but the reality completely denies that, as the products of these companies are environmental pollutants. Companies are able to achieve their environmental, social and economic sustainability through the application of modern production methods, including cleaner production, as one of the tools to address these environmental challenges effectively in order for bottled water producers’ companies to achieve business sustainabliliy. The importance of research stems from the fact that it deals with methods that preserve the natural environment and offer low-cost products while maintaining the quality of products, saving energy and preserving the safety of workers and society, hence, maximizing profits and improving the reputation and sustainability of the company. The study hypotheses were prepared and tested using a number of statistical tools. Study hypotheses were also evaluated using and then several results have concluded with a number of recommendations. Perhaps the most important ones are that the surveyed companies pay great attention to cleaner production processes in order to enhance competitiveness, with cleaner production and with a hope to achieving sustainable goals and constantly stay in the market.
Keywords: Cleaner ProductionBusiness SustainabilityBottled water Productioncompanies